Screening of Pharmacologically Active Small Molecule Compounds Identifies Antifungal Agents Against Candida Biofilms - Watamoto, Takao; Egusa, Hiroshi; Sawase, Takashi; Yatani, Hirofumi (Frontiers in Microbiology, 2015)
Candida species have emerged as important and common opportunistic human pathogens, particularly in immunocompromised individuals. The current antifungal therapies either have toxic side effects or are insufficiently effect. The aim of this study is develop new small-molecule antifungal compounds by library screening methods using C. albicans, and to evaluate their antifungal effects on Candida biofilms and cytotoxic effects on human cells. Wild-type C. albicans strain SC5314 was used in library screening. To identify antifungal compounds, we screened a small-molecule library of 1,280 pharmacologically active compounds (LOPAC1280TM) using an antifungal susceptibility test (AST). To investigate the antifungal effects of the hit compounds, ASTs were conducted using Candida strains in various growth modes, including biofilms. We tested the cytotoxicity of the hit compounds using human gingival fibroblast (hGF) cells to evaluate their clinical safety. Only 35 compounds were identified by screening, which inhibited the metabolic activity of C. albicans by >50%. Of these, 26 compounds had fungistatic effects and 9 compounds had fungicidal effects on C. albicans. Five compounds, BAY11-7082, BAY11-7085, sanguinarine chloride hydrate, ellipticine and CV-3988, had strong fungicidal effects and could inhibit the metabolic activity of Candida biofilms. However, BAY11-7082, BAY11-7085, sanguinarine chloride hydrate and ellipticine were cytotoxic to hGF cells at low concentrations. CV-3988 showed no cytotoxicity at a fungicidal concentration. Four of the compounds identified, BAY11-7082, BAY11-7085, sanguinarine chloride hydrate and ellipticine, had toxic effects on Candida strains and hGF cells. In contrast, CV-3988 had fungicidal effects on Candida strains, but low cytotoxic effects on hGF cells. Therefore, this screening reveals agent, CV-3988 that was previously unknown to be antifungal agent, which could be a novel therapies for superficial mucosal candidiasis.